Sparkle measurements for an automotive specification: Evaluation method for flexible setup conditions. Issue 9 (5th July 2022) - Rotscholl, Ingo; Schlipf, Andreas; Rickers, Christoph; Krüger, Udo
Abstract: This contribution proposes a sparkle evaluation based on a spatial frequency filter, taking into account various setup influences. Furthermore, the effect of flexible setup conditions on the reproducibility of measurement results is investigated. The procedure and concepts are derived for sampling resolutions between 15 and 30 cpx/mm with display pixel pitches between 183 and 224 ppi and validated by a round‐robin experiment with different test devices, including glass and foil‐based Anti‐Glare Layers. The findings serve as a basis for the measurement conditions of an automotive display sparkle measurement specification. Abstract : The effect of different sampling resolutions in sparkle measurements is considered by matching the evaluated frequency components to the viewing conditions. This allows more flexible setup conditions in sparkle measurements. The procedure and concepts are derived for sampling resolutions between 15 and 30 cpx/mm and validated by a round‐robin experiment with different test devices, including glass and foil‐based Anti‐Glare Layers.